Application of smart materials in health monitoring of civil infrastructures - Soh, Chee Kiong. (2008)
The last few decades have witnessed the construction of vast infrastructural facilities in Singapore and other parts of the world. Now, the ageing of these structures is creating maintenance problems and increasingly prompting the development of automated, real-time and online structural health monitoring (SHM) and non- destructive evaluation (NDE) systems, which can provide cost-effective alternative to the traditional visual inspection method. Similar necessity is increasingly felt for civil and military aircraft, spaceships, heavy machinery, trains, and so on, where long endurance combined with intensive usage causes gradual but unnoticed deterioration, often leading to unexpected disasters, such the as the Columbia Shuttle breakdown. The recent advent of ?smart? or ?intelligent? materials and structures technologies have ushered in a new avenue for the development SHM/ NDE systems. Smart piezoelectric-ceramic (PZT) materials, for example, have emerged as high frequency mechatronic impedance transducers (MITs) for SHM and NDE. As MIT, the PZT patches are not only robust, cost-effective, and show high damage sensitivity, but are also ideal for already constructed infrastructures and currently operational machinery because they only require non-intrusive external installation.